Quality of life in Europe First European Quality of Life Survey 2003 - Alber, Jens.; Delhey, Jan.; Keck, Wolfgang; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2004)
The enlargement of the European Union in May 2004 embraced 10 new Member States. A further enlargement may include four more. This puts diversity at the forefront of the European Union - diversity in living conditions, in cultural traditions and in outlook. Nurturing this cultural diversity is at the very heart of the European ideal. But large differences in material resources and living standards, in political participation rates, in levels of trust in public institutions and in how needs and responsibilities are understood, can lead to tensions and conflict.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: European federation -- Social aspects; Quality of life -- European Union countries; Electronic books